(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
India has been a significant source of human resources for many countries. However, it has also emerged as a destination for migrants from the African continent and neighboring Asian countries like Bangladesh, Nepal, Sri Lanka, and Myanmar, seeking education and work opportunities. However, this influx of migrants and immigrants has led to various social problems and political challenges that require urgent policy attention. Within the host country, immigrants often face unfavorable conditions, uncertainty, and instability. The social problems resulting from migration and immigration in India encompass poverty, acculturation, education, housing, employment, social adjustment, and family difficulties. These challenges demand a comprehensive understanding and effective policy measures. In addition to the social issues, immigration and migration have significant political consequences. Questions arise regarding political inclusion, political liberties, effects on political stability, and potential implications for conflicts and wars. It is essential to address these political aspects to ensure a harmonious and sustainable social and political environment. This paper delves into a thorough analysis of the social problems and political challenges arising from immigration and migration within India. It takes into account both international immigration and internal migration, providing a holistic perspective on the issue. To tackle the identified social problems and political challenges, this paper proposes policy statements that prioritize the interests of all stakeholders involved, including the host country, the country of origin, local communities, and the immigrants and migrants themselves. The aim is to foster an inclusive and cooperative approach towards addressing these issues effectively.